Malay/Indonesian at Hankuk University of Foreign Studies, Seoul, Republic of Korea - Zubaidah Ibrahim (Journal of Modern Languages)
Malaysia and Korea established diplomatic relations early in 1960  and in the 1980s Malaysia's "Look East Policy" led to the teaching of  Korean in Malaysia, and more than 10 years later the teaching of  Malay in Korea. Malay has been taught in Hankuk University of Foreign Studies for the past 11 years alongside Indonesian and a further 40 languages. This article gives a brief description of the historical background, curriculum, academic activities, availability of materials and references, the nature of the differences between the Malaysian and Indonesian varieties of the language and some of the problems which learners face as a result, and evaluation of student performance. The paper concludes with some thoughts about the way forward for the study of Malay as a foreign language in Korea and in Malaysia.